Founder retention as CEO at IPO in emerging economies: The role of private equity owners and national institutions - Hearn, Bruce; Filatotchev, Igor (Journal of Business Venturing, 2019)
We integrate the institutional perspective with research on the governance role of private equity firms in an investigation of Founder-CEO successions in Initial Public Offerings (IPOs) in emerging markets. Using a unique, hand-collected and comprehensive sample of 191 firms having undertaken IPOs in 21 markets across the African continent between January 2000 and August 2016, we apply instrumental variable (IV) Probit methodology and find that higher levels of private equity ownership are positively associated with the probability of the founder's retention as CEO, especially in the context of low-quality formal institutions. Further, in societies with high tribalism, higher private equity ownership is associated with an increased likelihood of founder retention. Voids in the institutional architecture underscore the importance of the founder as a key organizational resource for the firm and a source of institutionalized legitimacy, which in turn confers on the firm an ability to access required resources.